2011
DOI: 10.1016/j.tube.2010.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Local pulmonary immunotherapy with siRNA targeting TGFβ1 enhances antimicrobial capacity in Mycobacterium tuberculosis infected mice

Abstract: In this study we demonstrate that it is possible to shift the immune system during a chronic infection with Mycobacterium tuberculosis. TGFβ and IL10 cytokines inhibit the Th1 response during chronic pulmonary infection with M. tuberculosis. We show that intrapulmonary delivery of siRNA targeting TGFβ1 is able to reduce the pulmonary bacillary load in mice chronically infected with M. tuberculosis: an effect that appears to be partly dependent on IL10 expression. To demonstrate this, we induced gene silencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 38 publications
(41 reference statements)
1
36
0
Order By: Relevance
“…Aerosol delivery of siRNAs can affectively alter pulomary gene expression during experimental TB. 64,65 …”
Section: Discussionmentioning
confidence: 99%
“…Aerosol delivery of siRNAs can affectively alter pulomary gene expression during experimental TB. 64,65 …”
Section: Discussionmentioning
confidence: 99%
“…Further studies will define the most appropriate route of delivery, kinetics of miR-mimics/ anti-miR HDT as well as pharmacovigilance issues. The encouraging results reported for intranasal administration of miRs in lung cancer and those describing modulation of TGF-b1 expression via pulmonary delivery of siRNA in the TB mouse model [25], provide a valid basis for future miR-based HDTs. Detailed mechanistic insights into the biological role of miRs remain scarce, and specifics of modeof-action of anti-miR/miR-mimics await further clarification.…”
Section: Expert Opinionmentioning
confidence: 90%
“…In another study, intratracheal administration of lipid complex secreted protein, acidic and rich in cysteine and connective growth factor siRNAs are followed by a reduction in collagen fabrication in fibrotic lung tissues of bleomycin-induced mice [181]. Also, administration of anti-tissue growth factor-b1 (TGFb1) and chemokine (C motif) ligand (XCL1) siRNA also enhance anti-Mycobacterium tuberculosis effects in infected mice [182,183]. Despite all accomplished studies without any side effects, it is reported that siRNA cationic lipid (AtuFECT01) lipoplexes may create an inflammatory reaction in lungs [132].…”
Section: Current Pharmaceuticalsmentioning
confidence: 98%